2009
DOI: 10.1128/iai.00364-09
|View full text |Cite
|
Sign up to set email alerts
|

Outer Membrane Protein Expression Profile in Helicobacter pylori Clinical Isolates

Abstract: The gram-negative gastric pathogen Helicobacter pylori is equipped with an extraordinarily large set of outer membrane proteins (OMPs), whose role in the infection process is not well understood. The Hop (Helicobacter outer membrane porins) and Hor (Hop-related proteins) groups constitute a large paralogous family consisting of 33 members. The OMPs AlpA, AlpB, BabA, SabA, and HopZ have been identified as adhesins or adherenceassociated proteins. To better understand the relevance of these and other OMPs during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
79
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 51 publications
3
79
0
2
Order By: Relevance
“…Valkonen and colleagues found that N-acetylneuraminyllactose, sialylated fetuin, and certain other molecules significantly inhibited binding, suggesting an interaction between an H. pylori surface protein and glycosylated portions of laminin (59). Odenbreit and colleagues showed that mutation of the sabA gene in strain J99 abrogated laminin binding in a dot blot overlay assay, suggesting that SabA could also bind laminin (37). The sabA gene is reportedly not expressed in strain 26695 (37), and expression of sabA in strain SS1 has not been determined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Valkonen and colleagues found that N-acetylneuraminyllactose, sialylated fetuin, and certain other molecules significantly inhibited binding, suggesting an interaction between an H. pylori surface protein and glycosylated portions of laminin (59). Odenbreit and colleagues showed that mutation of the sabA gene in strain J99 abrogated laminin binding in a dot blot overlay assay, suggesting that SabA could also bind laminin (37). The sabA gene is reportedly not expressed in strain 26695 (37), and expression of sabA in strain SS1 has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Odenbreit and colleagues showed that mutation of the sabA gene in strain J99 abrogated laminin binding in a dot blot overlay assay, suggesting that SabA could also bind laminin (37). The sabA gene is reportedly not expressed in strain 26695 (37), and expression of sabA in strain SS1 has not been determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H. pylori also binds to sialyl-Lewis x via the SabA outer membrane protein (OMP) (10). H. pylori exhibits high genomic plasticity due to high rates of mutation and homologous recombination (11,12). Individual strains have been shown to modulate both their own adhesin expression and host glycan expression following infection (13,14).…”
mentioning
confidence: 99%
“…Interestingly, several of these variants were common for Latin American isolates regardless of which ancestral population they belonged to. AlpB is an adhesin binding to laminins in the extracellular matrix [22] that is present in all H. pylori strains [23]. Together with AlpA, it is required for colonization in experimental models and for efficient adhesion to gastric epithelial cells [24].…”
Section: Cc-by-ncmentioning
confidence: 99%